2004
DOI: 10.1177/147323000403200508
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Fracture Healing by Vitamin E in Rats

Abstract: We investigated the effects of the antioxidant alphae-tocopherol on early- and late-phase fracture healing in a rat model. Sixty male Sprague-Dawley rats were randomized into two groups. The right tibia of each rat was fractured manually under anaesthesia, and fracture sites fixed with intramedullary Kirschner wires. The alpha-tocopherol group received 20 mg/kg alpha-tocopherol intraperitoneally; the control group received intraperitoneal saline injections. Ten rats from each group were sacrificed on day 15, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
55
1
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 13 publications
1
55
1
3
Order By: Relevance
“…The strain of rats and the methods of lipid peroxidation measurement were also different from ours. Turk et al 25 have demonstrated reduction in the MDA levels in rats supplemented with a-tocopherol during the early phase of fracture healing. However, the MDA was measured indirectly in the serum, which represented the general oxidative status rather than the lipid peroxidation activity at the fracture site.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The strain of rats and the methods of lipid peroxidation measurement were also different from ours. Turk et al 25 have demonstrated reduction in the MDA levels in rats supplemented with a-tocopherol during the early phase of fracture healing. However, the MDA was measured indirectly in the serum, which represented the general oxidative status rather than the lipid peroxidation activity at the fracture site.…”
Section: Discussionmentioning
confidence: 99%
“…The dose of vitamin E and route of administration were also different from our study. Furthermore, Turk et al 25 studied normal fracture healing whereas we studied fracture in osteoporotic bone. All these factors may have contributed to the different findings of the MDA levels in their studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations